The Kingdom’s Shōnen Heart: Transcultural Character Design and the JRPG - Hutchinson, Rachael (Loading, 2022)
Taken by themselves, neither Disney nor Square Enix appears particularly successful at transcultural expression, although both are certainly marketing juggernauts in transmedia franchise operations (Smoodin, 1994; Consalvo, 2013). Disney may be understood in terms of American postwar cultural imperialism, while Square Enix is deeply rooted in conventions of Japanese storytelling. But together, somehow the two achieve a synergy in Kingdom Hearts (2002), coalescing in the figure of Sora, its youthful protagonist. This article performs a close reading of Sora’s visual character design, a transcultural melding of Walt Disney’s own Mickey Mouse and the shōnen figure of earlier Nomura Tetsuya creations. While gameplay dynamics point to a new action-adventure style for Square Enix, the shōnen characteristics of Sora’s appearance combine with his sense of loss and yearning to position the game in the JRPG genre.  Transculturality of the non-player characters (NPCs) in Kingdom Hearts is then considered. These character designs remain static, anchored to their original reference texts. Where the Disney characters fit their settings in an uncomplicated way, providing escapism and nostalgia for the player, Square characters seem to be chosen for their complexity. The use of then-recent Final Fantasy X characters Tidus and Wakka in Destiny Islands is contrasted against the use of darker, brooding characters from older Final Fantasy titles encountered later in the game. Just as loss and yearning define Sora’s shōnen character, the sense of loss manifested by Cloud, Aerith and Leon connect the player to the real-world context of the global late 1990s, speaking to Japanese anxiety following the Hanshin earthquake and Aum Shinrikyo attacks of 1995, and to the despair of ‘Generation X’ following Kurt Cobain’s death in 1994 (Funabashi and Kushner, 2015; Brabazon, 2005). Meanwhile, the deep economic recession of Japan’s ‘lost decade’ (1991-2001) connected perfectly to the post-9/11 unease in America at the time of the game’s release. Overall, I argue that the game’s success stems from its transcultural emphasis on loss and yearning, which fit not only the JRPG genre but also the sense of anxiety pervading both Japan and America at the time.